Proposta de Reorganização de um Estaleiro Público Militar: uma utilização do modelo de estrutura divisional - Takimoto, Alexandre Koji (2005)
The continuous changes in the industrial environment force its administrations to periodically rethink the organizational structure in order to verify if it is able to cope with the crescent challenges posed by the market and by the competition. The public administration organizations are, in general, less able to change quickly its structure but they also need to think about it and change it if necessary. This thesis analyzes the administrative structure of many shipyards, the theory of organization s structure, and the singularities of the analyzed shipyard, the Arsenal de Marinha do Rio de Janeiro. The result of this study is a proposal of a new administrative organization considering all the particularities with the purpose of increase efficiency.